Influencer marketing on social media in Palopo City: How sponsorship disclosure, influencer credibility, and MSME reputation influence promotional effectiveness‎ - Hayani, Nur; Iskandar, Ahmad Syarief; Ishak, Ishak (Journal of Islamic Economics Lariba, 2025)
IntroductionInfluencer marketing on social media has gained widespread attention for its ability to enhance promotional effectiveness by leveraging the authenticity and credibility of influencers. However, concerns about transparency, especially related to sponsorship disclosures, along with the credibility of influencers and businesses—particularly micro, small, and medium enterprises (MSMEs)—require deeper investigation, especially in emerging local markets.ObjectivesThis study investigates how sponsorship disclosure (explicit, implicit, or none), influencer credibility, and MSME credibility affect consumer perceptions and promotional effectiveness on social media. Additionally, the study examines the mediating role of consumer trust in these relationships within the context of MSMEs in Palopo City.MethodA quantitative approach utilizing a structured survey was employed. Data were collected from 133 active social media users in Palopo City who had experience interacting with influencer promotional content. Structural Equation Modeling (SEM) through SmartPLS software was used to analyze both direct and indirect effects among the study variables.ResultsFindings revealed that influencer credibility exhibited the strongest positive influence on promotional effectiveness, followed by MSME credibility and explicit sponsorship disclosure. Consumer trust significantly mediated these relationships, enhancing the overall impact of sponsorship disclosure, influencer credibility, and MSME credibility on promotional effectiveness.ImplicationsThe results underscore the importance for MSMEs to collaborate strategically with credible influencers and maintain transparency in sponsorship disclosures. Such practices can substantially increase consumer trust and, consequently, the effectiveness of promotional campaigns. Additionally, these findings highlight the necessity of regulatory support for transparent advertising practices.Originality/NoveltyThis research extends existing literature by exploring influencer marketing dynamics within a local MSME context, specifically examining how transparency in sponsorship disclosure, coupled with influencer and MSME credibility, influence promotional outcomes through consumer trust.